Long-term field performance of concrete produced with powder waste glass as partial replacement of cement - Nassar, Roz-Ud-Din (2021)
This paper reports the long-term field and laboratory-tested performance of concrete produced with 20 wt% replacement of cement with powder waste glass (WG). Field investigations of WG concrete were carried out in a large-scale field project comprising of various segments subjected to harsh weathering conditions and service load over a period of about three years. While laboratory cured WG concrete and normal concrete specimens were tested in compression and flexure at various concrete ages ranging from 3 days to 300 days. After about three years of field exposure, concrete cores were extracted from various segments of the project and tested for compressive strength, moisture sorption, and abrasion resistance. A detailed survey of the various segments of the project was carried out to physically examine the state of WG concrete after three years of service. Test results of the field WG concrete showed enhanced compressive strength, up to 57% reduction in moisture sorption and up to 61% reduction in abrasion weight loss in comparison to normal concrete at 300 days of concrete age. Similarly, the laboratory tests showed 43% gain in compressive strength and 28% gain in flexural strength of WG concrete in comparison to that of normal concrete at 90 days of concrete age. Detailed physical examination of various project segments showed no signs of deterioration or material failure after three years of service. The field project also demonstrated the constructability of WG concrete similar to that of normal concrete.